Trends in age- and sex-specific prevalence and incidence of cardiovascular disease in Western Australia. (29th August 2020) - Sarink, Danja; Nedkoff, Lee; Briffa, Tom; Shaw, Jonathan E; Magliano, Dianna J; Stevenson, Christopher; Mannan, Haider; Knuiman, Matthew; Hung, Joseph; Hankey, Graeme J; Norman, Paul; Peeters, Anna
Abstract: Background: Temporal trends in incidence and mortality of cardiovascular disease (CVD) have been well described, with recent data suggesting declining improvements in those aged under 55 years. However, little is known about the combined impact of incidence and mortality trends on disease prevalence, an important indicator of disease burden and cost. We analysed changes in age-specific and age-standardised temporal trends in prevalence and incidence of CVD subtypes. Methods: Annual prevalence and incidence rates of coronary heart disease, cerebrovascular disease and peripheral arterial disease for the Western Australian population for 1995–2010 were calculated using data from the Western Australian Data Linkage System. Joinpoint regression analyses were used to identify joinpoints in trends in age-specific and age-standardised annual prevalence and incidence rates for each CVD subtype. Results: Between 1995 and 2010, age- and sex-specific incidence and prevalence of the CVD subtypes generally decreased among middle-aged and older adults, but were stable or increased among younger adults. In < 55 year olds, increases in incidence tended to occur from 2003, while increases in prevalence were from 2007/2008. Declines in age-standardised incidence were greater than those in crude incidence, with changes in population structure having a greater impact among men than women. Conclusions: The majority of CVDs occurs in older adults. Our findings of generally worsening trends in prevalence in younger adults across most CVD subtypes were in contrast to generally declining trends in older age groups. These data highlight the importance of monitoring prevalence and incidence, particularly in younger adults.